The Dasavidha-Rājadhamma-Based Buddhist Leadership Approach: Its Influence on Organizational Citizenship Behavior - Ngailia, Munjiatul; Lestari, Diyah; Dharma, Guna; Ram, Su Dyana; Ardianto, Hendri; Meyliana, Henny (LPPM STIAB Jinarakkhita Lampung, 2024)
This study aims to analyze the influence of Buddhist leadership on organizational citizenship behavior (OCB) from the perspective of Dasavidha-Rājadhamma. Dasavidha-Rājadhamma is the ten virtues of leadership taught by the Buddha, including generosity, morality, honesty, and other virtues that are relevant in building harmonious and productive organizational relationships. This study uses a quantitative approach with an ex-post facto type. The study population consisted of 86 members of Buddhist assembly organizations, who were selected using a purposive sampling technique. Data was collected through a questionnaire based on the Likert scale that has been tested for validity and reliability. Data analysis was carried out using simple linear regression to test the influence of Buddhist leadership on the OCB. The results of the study show that Buddhist leadership has a significant influence on the OCB. This indicates that the principles in the Dasavidha-Rājadhamma can be an effective guide for leaders in improving the altruistic behavior, cooperation, and dedication of organizational members.